Kinetics of Growth and Amylase Production of Saccharomycopsis fibuligera on Potato Processing Wastewater - Lemmel, S. A. (1980)
The kinetics of growth and amylase production of Saccharomycopsis fibuligera were studied in a chemostat on a synthetic potato processing blancher water. Dilution rates (D) from 0.101 to 0.480 h(−1) were examined. A mathematical model based on the Monod equation was developed. The yield of cell mass from carbohydrates was constant and equal to 0.84. The maximum specific growth rate and the Monod constant were determined to be 0.596 h(−1) and 0.226 mg/ml, respectively. An equation for the steady-state starch concentrations was empirically derived. The steady-state noncarbohydrate carbon levels rose linearly with D. Reducing sugars were the growth-limiting substrate, and their steady-state levels conformed to Monod kinetics. The yield of amylase from the cell mass (Y(z)) declined as D rose and was described by the equation Y(z) = (−8.005D + 4.076). The model predicted that the maximum production of cell mass should occur at D = 0.35 h(−1) and the maximum production of amylase should occur at D = 0.22 h(−1). The mathematical model presented agreed with the experimental results in its prediction of the steady-state level of reducing sugar, starch, cell mass, and amylase concentrations as well as the productivity of amylase.